Adverse events in cryoballoon ablation for pulmonary vein isolation: Insight from the Food and Drug Administration Manufacturer and User Facility Device Experience - Min Choon Tan; Jian Liang Tan; Wei Jun Lee; Komandoor Srivathsan; Dan Sorajja; Hicham El Masry; Luis R. Scott; Justin Z. Lee (Journal of Arrhythmia, 2023)
Abstract Background Real‐world clinical data on the adverse events related to the use of cryoballoon catheter for pulmonary vein isolation remains limited. Objective To report and describe the adverse events related to the use of Artic Front cryoballoon catheters (Arctic Front, Arctic Front Advance, and Arctic Front Advance Pro) reported in the Food and Drug Administration's (FDA) Manufacturers and User Defined Experience (MAUDE) database. Methods We reviewed all the adverse events reported to the FDA MAUDE database over a 10.7‐year study period from January 01, 2011 to September 31, 2021. All events were independently reviewed by two physicians. Results During the study period, a total of 320 procedural‐related adverse events reported in the MAUDE database were identified. The most common adverse event was transient or persistent phrenic nerve palsy (PNP), accounting for 48% of all events. This was followed by cardiac perforation (15%), pulmonary vein stenosis (8%), transient ischemic attack or stroke (6%), vascular injury (4%), transient or persistent ST‐elevation myocardial infarction (3%), hemoptysis (2%), pericarditis (2%), and esophageal ulcer or fistula (1%). There were six reported intra‐procedural death events as a result of cardiac perforation. Conclusion The two most common procedural adverse events associated with cryoballoon ablation were PNP and cardiac perforation. All cases of procedural mortality were due to cardiac perforation.